الصلابة النفسية وعلاقتها بجودة الحياة المدرسية لدى أساتذة التعليم الإبتدائي - أحلام قدة; أحلام بوطيب; بكوش أحمد نجيب (جامعة الوادي - University of Eloued, 2025)
"ملخص الدراسة هدفت هذه الدراسة إلى الكشف على العلاقة بين الصلابة النفسية وجودة الحياة لدى أساتذة التعليم الابتدائي من خلال دراسة ميدانية على عينة قوامها (89) استاذ وأستاذة، تم اختيارهم بطريقة عشوائية من سبعة مدارس ابتدائية من المقاطعة رقم واحد بالرقيبة الوادي الجزائر، وذلك بإتباع خطوات المنهج الوصفي واستخدام استباني الصلابة النفسية وجودة الحياة تم تطبيقهم بعد التأكد من خصائصهم السيكو مترية. وأظهرت نتائج الدراسة: • وجود علاقة ارتباطية بين الصلابة النفسية وجودة الحياة لدى أساتذة التعليم الابتدائي. • لا توجد فروق ذات دالة إحصائية تعزى لمتغير الجنس بالنسبة للصلابة النفسية لدى أساتذة التعليم الابتدائي • لا توجد فرق ذات دالة إحصائية تعزى لمتغير الخبرة المهنية بالنسب لصلابه النفسية لدى أساتذة التعليم الابتدائي • توجد فروق ذات دالة إحصائية تعزى لمتغير الجنس بالنسبة لجوده الحياة لدى أساتذة التعليم الابتدائي • توجد فروق ذات دالة إحصائية تعزى لمتغير الخبرة المهنية بالنسبة لجوده الحياة لدى أساتذة التعليم الابتدائي "" This study aimed to discover the compatibility between psychological supervision and quality of life among primary school teachers through a field study in 89 primary schools in the first district of Reguiba El Oued, Algeria, following the steps of the Tunisia Established Critical Reliability and Quality of Life descriptive questionnaire, which were applied after drafting their psychometric applications. Delayed study results: There is a correlation between psychological resilience and quality of life among primary school teachers. There are no statistically significant differences attributable to the gender variable regarding psychological resilience among primary school teachers. There are no statistically significant differences attributable to the professional experience variable regarding psychological resilience among primary school teachers. There are statistically significant differences attributed to the overall quality of primary school teachers. There are statistically significant differences in the technical expertise of professional teachers compared to the overall quality of primary school teachers. "
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص علم نفس المدرسي
Keywords: ساتذة التعليم الإبتدائي; جودة الحياة; الصلابة النفسية; Mental resilience; quality of life; primary school teachers